Saline Water Bioleaching with Thermophilic Fe(Ii) Oxidizing Microorganisms - Corbett, M.; Collinson, D.; Shiers, D.; Kaksonen, A.; Watling, H.; Watkin, Elizabeth (Trans Tech Publications, Switzerland, 2015)
The chloride tolerance of three Fe (II)- and sulfur-oxidising thermophiles and the effect of chloride on metals extraction from mineral sulfides were studied. Initially, 10-day bioleaching tests (60 °C) were conducted using pyrite (FeS2), chalcopyrite (CuFeS2) or pentlandite ((Ni,Fe)9S8) concentrates as substrate in basal salts medium (BSM), and the activities of Sulfolobus (S.) metallicus, Acidianus (A.) brierleyi and Metallosphaera (M.) hakonensis were compared. Fe (II) oxidation, as indicated by an increase in oxidation reduction potential (ORP), was observed in all combinations except A. brierleyi growing on chalcopyrite. The presence of added NaCl resulted in lower ORP after 10 days of bioleaching in all cases. In ancillary tests using BSM-Fe (II) growth medium with added NaCl it was found that cell counts at the end of Fe (II) biooxidation provided the most reliable estimate of tolerance to NaCl. On this basis, the rank order of salt tolerance is S. metallicus >>>A. brierleyi > M. hakonensis.